(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Describes the inpatient experience at the Drug-Resistant Pulmonary Tuberculosis - HIV Tuberculosis Department of Son La provincial Lung Hospital in 2024. Participants: 150 inpatients at the Drug-Resistant Pulmonary Tuberculosis - HIV Tuberculosis Department of Son La provincial Lung Hospital from January 2024 to September 2024. Methods: A cross-sectional descriptive study was conducted. Data were collected using the patient experience assessment tool developed by the US Agency for Healthcare Research and Quality. Results: Most patients reported a positive experience with healthcare services. Specifically, 97.33% were satisfied with physician care, 94.67% rated nursing services highly, 94.67% expressed satisfaction with the hospital environment, and 92.67% had a clear understanding of post-discharge self-care. Factors such as health insurance coverage, educational level, and length of hospital stay were significantly associated with patient experience. Conclusion: The quality of services at the Drug-Resistant Pulmonary Tuberculosis - HIV Tuberculosis Department of Son La provincial Lung Hospital was highly rated. However, further efforts are needed to enhance patient education, improve the hospital environment, and optimize care processes to further improve patient experience.